The Method Of Training In Small - Sided Games In The Preparation Phase And Its Effectiveness On The Offensive Activation Of Football Players Under 17 Years Old From The Point Of View Of Some Coaches - Ben Rached, Yacine; Rabouh, Salah (sports creativity, 2025)
The study aimed to identify the effectiveness of small-sided games training in the preparation stage on the offensive activation in football for a group of under 17 years old from the point of view of some coaches, the estimated number of 20 professional coaches and the sample was chosen from the study population in a random manner, and the data was collected through an electronic form, as the researcher relied in this study on the descriptive approach to suit it with the current conditions that the world is going through, and by analyzing the results using the statistical packages program, the researcher concluded that training in small-sided games has an effectiveness on the offensive activation of football players under